Krytyka millenarystycznego obrazu Jerozolimy u św. Hieronima ze Strydonu - Paczkowski, Mieczysław (Vox Patrum, 2020)
The purpose of this study is to examine St. Jerome’s critical disposition towards the millenarian image of Jerusalem. In the set of controversies addressed by Jerome, the topic is worthy of interest. He opposed the Chiliastic tendencies shown by the Judaizing exegetes and confronted authors who distorted the message of the biblical images. However, we can see that the author of the Vulgate reached for the legacy of the exegetical tradition prescribing literal reading. In Jerome we find a dual perspective of Jerusalem’s renewal: as both an earthly and glorious city in the heavens. Some shepherds of the communities also considered this issue, such as Victorinus of Poetovium and Apollinaris of Laodicea. The pages devoted to the millenarian question in Jerome’s writings testify that he was implicated in this controversy for various reasons.